Development of the Russian socio-economic system: challenges and prospects - Kiselev A. A., Soldatova L. I., Shmidt I. I., Fadeeva G. V., Boboshko A. A., Kharlanov A. S., Lapshin V. I., Beketova O. N., Sedov I. D., Bagirova A. R., Loseva E. S., Fedorova I. A., Dashian S. G., Fedulova E. A., Burtseva E. V., Medvedeva S. V., Ivaniuzhenko A. B., Shchankina L. N., Voronenko E. A., Piatitskaia D. V., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Sych G. V., Lavina T. A., Gritsevich T. I., Russova N. V., Zakharova A. N., Paevskaia S. L., Mironova N. G. (Development of the Russian socio-economic system: challenges and prospects, 2024)
the chapter highlights innovative models for the formation of training of engineering personnel in the higher education system of the Russian Federation, identified on the basis of an analysis of materials from federal innovation plans. The work was carried out within the framework of the Research Agreement on "Identification of best practices based on the results of expert evaluation of applications and reports of federal innovation platforms" with LLC "Financial Expert Systems". Moscow, the operator of the organization of the procedure for evaluating the activities of FIP entities within the framework of the execution of the State Contract dated April 25, 2022 No.05.2022.244.02.003.021 for the performance of works (provision of services) under the project "Information, analytical and technological support for the formation and functioning of a network of federal innovation platforms in the advanced educational ecosystem of the Russian Federation". The authors consider projects of federal innovation platforms of institutions of higher education, implemented in the field of engineering education, as well as in other interdisciplinary areas related to the training of engineering personnel in modern conditions.
Keywords: инженерное образование; engineering education; федеральные инновационные площадки; учреждения высшего образования; federal innovation platforms; higher education institutions; инновационные образовательные проекты; инновационные модели; innovative educational projects; innovative models; Приоритетный национальный проект «Образование»; Приоритетный национальный проект «Наука и университеты»; Priority national project "Education"; Priority national Project "Science and Universities"